2015
DOI: 10.3390/bios5010085
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Sensing of Adenosine Based on Force Variations Induced by Molecular Recognition

Abstract: We demonstrate a simple force-based label-free strategy for the highly sensitive sensing of adenosine. An adenosine ssDNA aptamer was bound onto an atomic force microscopy (AFM) probe by covalent modification, and the molecular-interface adsorption force between the aptamer and a flat graphite surface was measured by single-molecule force spectroscopy (SMFS). In the presence of adenosine, the molecular recognition between adenosine and the aptamer resulted in the formation of a folded, hairpin-like DNA structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…This phenomenon may, for example, result in the different behavior reported for the interaction of ssDNA and dsDNA with solid surfaces. With a highly flexible backbone and lack of defined secondary structure, ssDNA is thought to bind strongly to graphene and carbon nanotube (CNT) substrates. ,,, ,, Accordingly, the consensus prediction from molecular dynamics (MD) simulations is that ssDNA adsorbs in a flat conformation with a majority of the nucleobases in direct contact with the substrate, although interbase interactions have been found to be important in some cases. In contrast, dsDNA (and regions of ssDNA possessing well-defined secondary structure) tend to interact more weakly with CNTs and graphene, with the interfacial molecular structure relatively less affected by the adsorption process. ,,,, Also, the molecular-level structure of the interaction of dsDNA/dsRNA with graphene interfaces appears less clear than in the case of ssDNA, with previously proposed surface-binding modes of dsDNA including an upright orientation via surface contact with the 3′ and 5′ terminal bases, or in a parallel orientation. ,,,, Overall, the interaction of oligonucleotides with graphitic substrates therefore depends on the balance between nucleotide base pairing, nucleotide π–π interactions, backbone flexibility, and nucleotide–substrate π–π interactions. In many instances, DNA aptamers may contain both regions of dsDNA and ssDNA, and therefore the molecular-scale details of the aptamer–graphene interaction may depend strongly on the nature of the aptamer.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…This phenomenon may, for example, result in the different behavior reported for the interaction of ssDNA and dsDNA with solid surfaces. With a highly flexible backbone and lack of defined secondary structure, ssDNA is thought to bind strongly to graphene and carbon nanotube (CNT) substrates. ,,, ,, Accordingly, the consensus prediction from molecular dynamics (MD) simulations is that ssDNA adsorbs in a flat conformation with a majority of the nucleobases in direct contact with the substrate, although interbase interactions have been found to be important in some cases. In contrast, dsDNA (and regions of ssDNA possessing well-defined secondary structure) tend to interact more weakly with CNTs and graphene, with the interfacial molecular structure relatively less affected by the adsorption process. ,,,, Also, the molecular-level structure of the interaction of dsDNA/dsRNA with graphene interfaces appears less clear than in the case of ssDNA, with previously proposed surface-binding modes of dsDNA including an upright orientation via surface contact with the 3′ and 5′ terminal bases, or in a parallel orientation. ,,,, Overall, the interaction of oligonucleotides with graphitic substrates therefore depends on the balance between nucleotide base pairing, nucleotide π–π interactions, backbone flexibility, and nucleotide–substrate π–π interactions. In many instances, DNA aptamers may contain both regions of dsDNA and ssDNA, and therefore the molecular-scale details of the aptamer–graphene interaction may depend strongly on the nature of the aptamer.…”
mentioning
confidence: 55%
“…However, we note here that these experiments were conducted for the graphene oxide substrate, which might yield very different outcomes than those generated for a graphene substrate. Furthermore, recent experimental efforts based on atomic force microscopy (AFM), namely, single molecule force spectroscopy (SMFS), investigated the interaction of this aptamer with the aqueous graphite interface . These SMFS experiments showed that by pulling the surface-adsorbed aptamer from aqueous graphite interface ,,, this produced a stable force plateau in the measured force–distance curves, which can be interpreted as representing the successive, base-by-base desorption of the strand from the surface.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The detection method demonstrated in this study showed immense potential to develop more drug sensors. In another recent study, AFM force-based sensor was developed (Li J et al, 2015) for the detection of adenosine with higher sensitivity and probe the molecular recognition events between DNA aptamer and adenosine. This label-free detection procedure provides an easier and less timeconsuming way of identification of other similar chemical molecules.…”
Section: Sensing Of Drug Moleculesmentioning
confidence: 99%
“…Firstly, SMFS technique can be utilized to fabricate highly sensitive sensor platforms for detecting DNA, RNA, protein, enzyme, drug molecules, and metallic ions. Readers are suggested to study our previous review on the SMFS-based bioimaging and biosensing [25,92,93]. Here several recent studies on SMFS-based biosensing are introduced.…”
Section: Potential Applicationsmentioning
confidence: 99%